Oxygen and Nutrient Trapping in the Southern Benguela Upwelling System - Rixen, Tim; Lahajnar, Niko; Lamont, Tarron; Koppelmann, Rolf; Martin, Bettina; van Beusekom, Justus E. E.; Siddiqui, Claire; Pillay, Keshnee; Meiritz, Luisa (Frontiers in Marine Science, 2021)
The Benguela Upwelling System in the southeast Atlantic Ocean is of crucial socio-economic importance due to its high productivity. However, predicting its response to global change and understanding past changes are still great challenges. Here, we compile data obtained from a research cruise and an oceanographic mooring to demonstrate that a topographically steered nutrient trapping zone develops in a narrow belt along the coast during the main upwelling season in austral spring and summer in the southern Benguela Upwelling System. High nutrient concentrations within this zone increase the impact of upwelling on the productivity of the southern Benguela Upwelling System, but the efficient nutrient trapping operates at the expense of decreasing oxygen concentrations. This enhances the probability of anoxic events emerging toward the end of the upwelling season. However, at the end of the upwelling season, the front that separates the coastally trapped waters from open shelf waters weakens or even collapses due to upwelling cessation and the reversing current regime. This, in addition to a stronger vertical mixing caused by winter cooling, fosters the ventilation of the nutrient trapping zone, which reestablishes during the following upwelling season. The postulated intensification of upwelling and changes in the ecosystem structure in response to global warming seem to reduce the nutrient trapping efficiency by increasing offshore advection of surface waters and plankton blooms. The intensified upwelling and resulting lower biological oxygen consumption appears to mask the expected impacts of global warming on the oxygen minimum zone (OMZ) in the southern Benguela Upwelling System. In contrast to other OMZs, including those in northern Benguela Upwelling Systems, the OMZ in the southern Benguela Upwelling System reveals so far no detectable long-term decrease in oxygen. Thus, the nutrient trapping efficiency seems to be a critical feature mitigating global change impacts on the southern Benguela Upwelling System. Since it is topographically steered, regional impacts on the nutrient trapping efficiency appear also to explain varying responses of upwelling systems to global change as the comparison between southern and northern Benguela Upwelling System shows. This emphasizes the need for further and more comparable studies in order to better understand the response of Eastern Boundary Upwelling Systems and their ecosystem services to global change.